PENGUKURAN TINGKAT IMPLEMENTASI REKOMENDASI HASIL KAJIAN KINERJA LINGKUNGAN PADA LIMA UKM DI SURABAYA - Yulfiah Yulfiah (Department of Environmental engineering, Faculty of Science and Technology, Islamic State University Sunan Ampel Surabaya, 2019)
Actually Small Medium Enterprises (SMEs) in the city of Surabaya give negative contributions to the environment. Related to this, two studies have been conducted to help overcome the negative impact. The first stage of the study was analyzed environmental performance of SMEs in Surabaya. As a result of the study, recommendations for activities for SMEs have been formulated to be more pro-environment. The next phase of the second phase of the research, which consists of the level of implementation of the assessment that has been given, the results that can be done regarding the discussion carried out. The results of the second phase of research that discusses the level of implementation of the assessment given to SMEs varies from 50-90%. Thus, SME awareness to make its company a Pro Environment company still has to improve. The formulation of an educational model for SMEs is needed, so that the environmental performance carried out is not limited to passing legislation. Moreover, the performance of the environment implemented by the company is approved, because it provides a larger company and environmental sustainability.